Pengelolaan Media Pembelajaran Matematika Kelas V SD Negeri Banyuanyar I Surakarta - Sukiman, Sukiman, Dr. Sumardi, M.Si, Dr. Tjipto Subadi, M.Si (2017)
The study has two objectives. 1. Describing the management of Mathematics learning media for the fifth grade students of SDN Banyuanyar I Surakarta. 2. Describing the supporting factors and obstacles in the management of Mathematics learning media for the fifth grade students of SDN Banyuanyar I Surakarta. The research is descriptive research by giving a real idea dealing with the management of Mathematics learning media for the fifth grade students of SDN Banyuanyar I Surakarta. The data collection techniques used in the research are observation, interview, and documentation. While the data analysis technique used in the research is interactive model. There are two results of the research: 1) the management of Mathematics learning media for the fifth grade students of SDN Banyuanyar I Surakarta is quite effective and productive, where the teaching and learning process involves the components of learning and the objective can be reached optimally. There are some plans prepared for the learning media. They are: determining the learning materials and formulating the learning objectives, selecting and organizing the materials, media, and sources, designing learning scenario, designing classroom management, designing procedure and preparing assessment, and the assessment which will be carried out. The implementation of learning, teaching and the implementation of learning media refers to how a teacher can maximize the learning media as what he/she has planned before in his/her planning. The implementation of learning management uses some steps: opening the class, delivering the learning materials, and closing the class. The evaluation of the learning is done in order to obtain information about the fifth grade students' achievement. 2) The supporting factors found in the management of Mathematics learning media for the fifth grade students of SDN Banyuanyar I Surakarta are: the curriculum, the building and class facilities, the teachers and students. The facilities used for learning media can establish Math learning process effectively and productively. The physical class condition, ventilation, temperature, seating, tables, and other tools support the efficacy of using the learning media. The obstacle faced in implementing the learning media for teaching Mathematics is the distinction of the students mental and characteristics. The way to overcome the obstacle stated before is by doing approach to the students and their parents. The solution to maintain the media is by placing the media in the right place which has already prepared and reminding all the teachers who use the media to return them into the right place and arrange them well.